The Effect of Using Information Technology, User Involvement, and Support from Top Management on Performance of Accounting Information System - Wage Muhammad Taufik (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
AbstractThis research was conducted to provide empirical evidence about the effect of using information technology, user involvement, and support from top management on the performance of the accounting information system. This research uses primary data obtained from distributing questioner to 60 accounting/finance employee that works in 7 company which located in Jakarta Industrial Estate Pulogadung. The sampling technique used in this research is random sampling and analyzed by SPSS application version 24. This research uses multiple linear regression analysis methods and the signs used in testing hypotheses were 5%. Based on the results of the research showed that using information technology and support from top management had a significant effect on the performance of the accounting information system while user involvement did not affect the performance of accounting information system. AbstrakPenelitian ini dilakukan untuk memberikan bukti empiris tentang pengaruh penggunaan teknologi informasi, keterlibatan pengguna, dan dukungan dari manajemen puncak terhadap kinerja sistem informasi akuntansi. Data primer diperoleh dari penyebaran kuisioner kepada 60 pegawai akuntansi/keuangan yang bekerja di 7 perusahaan yang berlokasi di Kawasan Industri Jakarta Pulogadung. Teknik pengambilan sampel yang digunakan adalah random sampling dan dianalisis dengan aplikasi SPSS versi 24. Penelitian ini menggunakan metode analisis regresi linier berganda dan tanda-tanda yang digunakan dalam pengujian hipotesis adalah 5%. Hasil penelitian menunjukkan bahwa menggunakan teknologi informasi dan dukungan dari manajemen puncak berpengaruh signifikan terhadap kinerja sistem informasi akuntansi sedangkan keterlibatan pengguna tidak mempengaruhi kinerja sistem informasi akuntansi.